Perubahan Ideologi Tokoh Utama dalam Novel Ar-Rojul Al-Ladzi Amana Kajian Fenomenologi Edmund Husserl - Rarasati, Indah; Zawawi , Moh.; Huda , Khoirul (Institut Agama Islam Negeri Metro, 2024)
Phenomenology comes as a scientific approach that aims to examine and describe a phenomenon experienced directly by humans in their daily lives. The purpose of this research is to find out the socio-cultural background in the novel Ar-Rojul Al-Ladzi Amana, interpret and describe the factors that cause changes in the main character's ideology and reveal changes in the life views and thoughts of the main character in the novel Ar-Rojul Al-Ladzi Amana using Edmund Husserl's phenomenology. The method used in this research is descriptive qualitative by analyzing social events, phenomena, or circumstances based on quotations found in the novel Ar-Rojul Al-Ladzi Amana. from the research that has been done, researchers found the results, namely: 1) the difference in life between Italy and Dubai experienced directly by Eryan as the main character has an attachment to changes in his religious ideology; 2) there are three factors that influence the ideology of the main character; 3) there are seven changes in Eryan's outlook on life and thought after knowing Islam.